(untitled) (Colombia Medica, 2012)
Objectives: To describe the changes occurred in some sociodemographic variables and in the living conditions among the Nasa, Guambiana and Afrocolombian populations in the northern region of the department of Cauca, and those occurred in two white-mestizo and black residential sectors in Cali, during the 1993-2005 period. Methods: It is a descriptive study for which several sociodemographic indicators were calculated through the processing of census microdata of the years 1993 and 2005: juvenile dependency rate; total masculinity index; mean household size; specific and global fecundity, and infant mortality rates; life expectancy; mean years of schooling; health coverage; and percentage of population with unmet basic needs (UBN). In this way, the notorious differences in the sociodemographic and standard of living trends between the different populations under study can be stressed. Results: The Guambiana population of the Silva town presents lower fertility rates than the Nasa population, still characterized for presenting early fertility rates. Unlike the northern Cauca Indian people, the Afrocolombian population from this region and the one resident in Cali’s black popular urban classes tends to show similar socio-demographic patterns. Conclusions: Although there have been deep changes during this period among the populations under study, the ethnic-racial inequalities seem to persist. From this first diagnosis, attention is called to the need for a more adequate reproductive health policy to attend the specific needs present among the Indian population.